Fostering Interprofessional Education During Required Clerkships for Medical Students Across Regional Campuses - Stephanie Freed; Deborah R. Birnbaum; Jennifer Schwartz; Paul Ko; Megan Christman; Paul Wallach (Journal of Regional Medical Campuses)
It remains complex and challenging to deliver interprofessional education at medical schools with geographically distributed campuses. Indiana University School of Medicine (IUSM) expanded its interprofessional education directly into clinical training by implementing a simple exercise in required clerkships on all nine of its campuses and with various health system partners that achieves the goals of interprofessional education and in which students find value.